Dormant‐Season Planting and Seed‐Dormancy Impacts on Switchgrass Establishment and Yield. Issue 1 (1st January 2016) - Keyser, Patrick D.; Ashworth, Amanda J.; Allen, Fred L.; Bates, Gary E.
ABSTRACT: Establishment failures linked to seed dormancy are a challenge to wide‐scale use of switchgrass ( Panicum virgatum L.) for biomass feedstock and forage production. One prospective strategy for breaking dormancy is dormant‐season planting. The objectives of this study were to evaluate (i) three switchgrass dormant‐season planting dates (1 December, 1 February, and 15 March) vs. a growing‐season (1 May) control; (ii) two seeding rates (6.7 and 10.1 kg pure live seed [PLS] ha −1 ); and (iii) high‐ and low‐dormancy seed lots. Treatments were assigned in a split‐plot design with three replications at two locations in Tennessee in 2008 and 2009. Neither seeding rate nor seed‐dormancy level affected plant density or yield ( P > 0.05). However, a seeding date × year interaction impacted first‐year density at both locations. Although patterns differed by year for the two locations, density of March plantings equaled or exceeded ( P < 0.05) those at other dates for both locations and years. These variations in density did not carry over to impact yield in year two. A sigmoidal regression of seedling density vs. yield was significant ( P < 0.001) albeit not strong ( R 2 = 0.13); yield response approached an asymptote above ∼8 plants m −2 . Results suggest March planting dates, using standard seeding rate recommendations (6.7 kg PLS ha −1 ) irrespective of seed‐dormancy rates, may be more reliable than planting in May. Thus, a broader establishment window than traditionally used may be practical. However, results should be validated over a broader range of soils and climatic conditions, especially over a winter severity gradient.